2010
DOI: 10.1111/j.1744-7410.2010.00207.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene and species trees reveal mitochondrial and nuclear discordance in the Drosophila cardini group (Diptera: Drosophilidae)

Abstract: Abstract. The Drosophila cardini group includes 15 species, which are subdivided into the D. cardini and D. dunni subgroups. Although many phylogenetic hypotheses have been proposed for this group during the last five decades (based on patterns of reproductive isolation, morphology of male genitalia, chromosomal inversions, isozyme variation, or molecular sequence data), these are mostly discordant with each other. We aimed to clarify some of the evolutionary patterns related to the origin of this incongruenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…Generally, for all taxa examined, the Greater Antilles harbor more species than the Lesser Antilles, and the larger Greater Antilles islands, like Cuba and Hispaniola, typically have more species than the smaller islands of Puerto Rico and Jamaica. This expected pattern of Cuba > Hispaniola > Jamaica > Puerto Rico generally holds for the bug family Lyagaeidae [56], pseudoscorpions [91], scaritine beetles [92], Centruroides scorpions ( Fig. 11), Micrathena spiders (Fig.…”
Section: Species-area Relationships and Endemismmentioning
confidence: 71%
“…Generally, for all taxa examined, the Greater Antilles harbor more species than the Lesser Antilles, and the larger Greater Antilles islands, like Cuba and Hispaniola, typically have more species than the smaller islands of Puerto Rico and Jamaica. This expected pattern of Cuba > Hispaniola > Jamaica > Puerto Rico generally holds for the bug family Lyagaeidae [56], pseudoscorpions [91], scaritine beetles [92], Centruroides scorpions ( Fig. 11), Micrathena spiders (Fig.…”
Section: Species-area Relationships and Endemismmentioning
confidence: 71%
“…This incongruence between the mitochondrial DNA and nuclear DNA is expected due to differences in parental inheritance and effective size (mitochondrial with effective population size four times smaller than nuclear) (Funk and Omland, 2003;Toews and Brelsford, 2012), and several studies have shown this mitonuclear disagreement (Gompert et al 2008;Franco et al 2015, Ré et al 2010Després, 2019). Furthermore, differences have been found in the selective pressure of the mitochondrial genome compared to the nuclear genome (Toews and Brelsford, 2012;DeBiasse et al 2014), corroborating our data.…”
Section: Phylogenetic Incongruencesupporting
confidence: 91%
“…We then used these virgin flies to mate all species in pairwise combinations individually in 3 replicates. For each replicate we mated 10 males with 10 females (all aged 2–3 days) for 5 days ( Wilder and Hollocher 2003 ; Cenzi De Ré et al 2010 ). Following the 5-day mating period and removal of the parents, we collected offspring every day for 30 days.…”
Section: Methodsmentioning
confidence: 99%